Analytical psychology : a modern science - Fordham, Michael, 1905-1995 (Library of analytical psychology, 1973)
Analytical Psychology: A Modern Science discusses the fundamental concepts of analytical psychology and presents clinical studies. The book is comprised of 14 chapters that are organized into two parts. The first part covers the basic concepts and theoretical basis of analytical psychology. Concepts such as symbols, archetypes, and ego are covered in the first part. The text also covers the importance of analyzing childhood. Next, the book presents some clinical studies. Cases such as the incapacity to imagine and sense of time are discussed. The text will be of great interest to students, res.